2020
DOI: 10.3390/app10207374
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effects of Ethanol Extract of Ziziphus jujuba Mill Seeds in Mice

Abstract: The antidepressant-like activity of ethanol extract of Ziziphus jujuba Mill var. spinosa seeds (Semen Ziziphi Spinosae, SZS) was investigated by behavioral tests, such as a forced swimming test (FST), a tail-suspension test (TST), and an open field test (OFT), using mice exposed to chronic unpredictable mild stress (CUMS). In the TST, immobility times of the extract-treated groups E100 and E300 (CUMS + 100 and 300 mg/kg extract, respectively) were significantly decreased in a dose-dependent manner compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Oh et al reported that ethanol extract of Ziziphus jujuba Mill var. Spinosa seeds exhibited significant anti-depressant-like effects by increasing the mobility time and total distance in the force swimming and open field tests ( 32 ). In previous studies, pretreatment with an aqueous extract of B. serrata enhances the rats' performances in the Morris water maze and open field tests and corrects memory impairment in LPS-induced inflammation ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al reported that ethanol extract of Ziziphus jujuba Mill var. Spinosa seeds exhibited significant anti-depressant-like effects by increasing the mobility time and total distance in the force swimming and open field tests ( 32 ). In previous studies, pretreatment with an aqueous extract of B. serrata enhances the rats' performances in the Morris water maze and open field tests and corrects memory impairment in LPS-induced inflammation ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sejalan dengan beberapa penelitian yang menyebutkan bahwa tanaman bidara memiliki efek antidepresan. 23,24,25 Dipercaya bahwa komponen pada ekstrak bidara bekerja melalui sistem serotonergik and noradrenergik untuk memberikan efek anticemas dan antidepresi. 25…”
Section: Analisis Gc-ms Ekstrak Daun Bidaraunclassified
“…Naïve male Institute of Cancer Research (ICR) mice (n = 8 per group; age, 5 weeks; weight, 25-30 g) were supplied by ORIENT BIO (Seongnam, Republic of Korea). Animals were housed in standard conditions: temperature at 25 ± 2 • C, relative humidity at 60 ± 10%, under a 12 h light (07:00-19:00)/12 h dark cycle [49,50]. Animals were randomly divided into 5 groups: control, negative (5 mg/kg scopolamine, Scop); positive (Scop + 5 mg/kg donepezil), low-dose MC (Scop + 5 mg/kg MC), and high-dose MC (Scop + 15 mg/kg MC).…”
Section: Animals and Administrationmentioning
confidence: 99%